2022
DOI: 10.21203/rs.3.rs-2214116/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of dietary hemp seed meal as soybean meal substitution on productive performance, egg quality, and yolk fatty acid composition of laying hens

Abstract: Hemp seed meals contain high protein and unsaturated fatty acids which have the potential as a substitute for soybean meal and yield eggs rich in unsaturated fatty acids. Therefore, the study aimed to evaluate the impact of dietary hemp seed meal as a substitute for soybean meal protein on productive performances, egg quality, and yolk fatty acid composition. A total of 120 Lohmann Brown laying hens aged 50 weeks were separated into 4 groups and 10 repetitions with 3 birds each. Birds received treatment withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(25 reference statements)
0
1
1
Order By: Relevance
“…However, Neijat et al [ 16 ] reported that adding 10% hemp seeds to the diets of laying hens did not affect the laying rate but reduced the egg weight. Also, our findings contrast with those of other studies that found that including 8% and 12% hemp seeds in the diets of laying hens had a negative impact on egg production and feed efficiency (FCR) [ 44 ]. These differences may be due to the fact that a newly developed variety of hemp seeds in Turkey was used in the previous study, which may have a higher content of anti-nutrients, exceeding the tolerable limits of laying hens.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, Neijat et al [ 16 ] reported that adding 10% hemp seeds to the diets of laying hens did not affect the laying rate but reduced the egg weight. Also, our findings contrast with those of other studies that found that including 8% and 12% hemp seeds in the diets of laying hens had a negative impact on egg production and feed efficiency (FCR) [ 44 ]. These differences may be due to the fact that a newly developed variety of hemp seeds in Turkey was used in the previous study, which may have a higher content of anti-nutrients, exceeding the tolerable limits of laying hens.…”
Section: Discussioncontrasting
confidence: 99%
“…The yolks of the eggs from the hens fed diets containing dried fruit pomace (HB and HR) were found to be more intensely colored (higher RYCF score) than yolks of the eggs from the control group ( Table 4 ). This color improvement is caused by the carotenoids, xanthophylls, and chlorophylls in the pomace, which are transferred to the yolks [ 44 ]. In the present study, the color score was higher for the HR eggs than for the HB eggs.…”
Section: Discussionmentioning
confidence: 99%